1975
DOI: 10.1111/j.1751-1097.1975.tb06632.x
|View full text |Cite
|
Sign up to set email alerts
|

DETERMINATION OF THE pk VALUES OF THE LUMIFLAVIN TRIPLET STATE BY FLASH PHOTOLYSIS

Abstract: Lumiflavin was prepared by photolysis of an alkaline aqueous solution of riboflavin (Knowles and Roe, 1968). As a solvent we used triply distilled water, as buffers (0,2 M) (Schwabe, 1958): pH 1-3'7 sodium acetate, hydrochloric acid pH 3·7-5·6 sodium acetate, acetic acid pH 6-12 potassium dihydrogen phosphate, sodium hydroxide pH 13 potassium chloride, sodium hydroxide (E. Merck. Darmstadt, Germany). RESULTSDependence of the lumiflavin triplet -triplet absorption spectrum on pH. Figure I shows the transient ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
1

Year Published

1980
1980
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 20 publications
5
40
1
Order By: Relevance
“…Keeping these precautions in mind we found that flashing 15 pM flavin for microseconds lead to 100% foi-mation of flavoquinone triplet (3Fl$x) at pH > 6 (A, , , = 690 nm, E = 4400 cm-I M-') and to the conjugate acid ('HFl : : ) at pH < 5 (A, , , = 670 nm, E = 4800 cm-' M-l) [13,17]. The entire transfer of flavin into the excited triplet state results from multiple excitation of FI,, by the highly intense flash light, since the actual lifetime of the excited flavin singlet (zf = 6.9 ns for 3-methyllumiflavin [18]) is much shorter than the flash duration ( Fig.…”
Section: Flash Photolysis Of Flavin In Aqueous Buifer: Fi As Donormentioning
confidence: 99%
See 3 more Smart Citations
“…Keeping these precautions in mind we found that flashing 15 pM flavin for microseconds lead to 100% foi-mation of flavoquinone triplet (3Fl$x) at pH > 6 (A, , , = 690 nm, E = 4400 cm-I M-') and to the conjugate acid ('HFl : : ) at pH < 5 (A, , , = 670 nm, E = 4800 cm-' M-l) [13,17]. The entire transfer of flavin into the excited triplet state results from multiple excitation of FI,, by the highly intense flash light, since the actual lifetime of the excited flavin singlet (zf = 6.9 ns for 3-methyllumiflavin [18]) is much shorter than the flash duration ( Fig.…”
Section: Flash Photolysis Of Flavin In Aqueous Buifer: Fi As Donormentioning
confidence: 99%
“…The common feature in light-excited and dehydrogenase flavins is apparently the induction of basic character either by an auxiliary basic protein group [30,31] or by the intrinsic basicity generated in the triplet 3Fl,*, [13] which both help to split a substrate KH into R -and H', formally.…”
Section: (13)mentioning
confidence: 99%
See 2 more Smart Citations
“…This high pH values (pH > 10). [55] Under these conditions, significant deprotonation of the dimer unit occurs (pK a ϭ 10.7), [56] quantum efficiency allowed the group to obtain a pH profile of the chain reaction. This study revealed half maximum which led to the proposal that electron transfer from the deprotonated dimer to the oxidized, light-excited flavin dimer cleavage at pH ഠ 7.5 and maximum splitting efficiency at pH ഠ 8.5.…”
Section: Previous Experiments With Flavin and Flavin Dimer Solutionsmentioning
confidence: 99%